Stability of Negative Solitary Waves for a Generalized Camassa-Holm Equation with Quartic Nonlinearity - Shan Zheng; Zhengyong Ouyang (Advances in Mathematical Physics)
We consider the stability of negative solitary waves to a generalized Camassa-Holm equation with quartic nonlinearity. We obtain the existence of negative solitary waves for any wave speed c>0 and some of their qualitative properties and then prove that they are orbitally stable by using a method proposed by Grillakis et al.